The interplay between the microbiota and opioid in the treatment of neuropathic pain - Gong, Zexiong; Xue, Qingsheng; Luo, Yan; Yu, Buwei; Hua, Bo; Liu, Zhiheng (Frontiers in Microbiology, 2024)
Neuropathic pain (NP) is characterized by its complex and multifactorial nature and limited responses to opioid therapy; NP is associated with risks of drug resistance, addiction, difficulty in treatment cessation, and psychological disorders. Emerging research on gut microbiota and their metabolites has demonstrated their effectiveness in alleviating NP and augmenting opioid-based pain management, concurrently mitigating the adverse effects of opioids. This review addresses the following key points: (1) the current advances in gut microbiota research and the challenges in using opioids to treat NP, (2) the reciprocal effects and benefits of gut microbiota on NP, and (3) the interaction between opioids with gut microbiota, as well as the benefits of gut microbiota in opioidbased treatment of NP. Through various intricate mechanisms, gut microbiota influences the onset and progression of NP, ultimately enhancing the efficacy of opioids in the management of NP. These insights pave the way for further pragmatic clinical research, ultimately enhancing the efficacy of opioid-based pain management.